Agro‐waste areca nut husk and bagasse fiber reinforced epoxy‐based hybrid composite for thermal insulated false ceiling application - Rois Uddin Mahmud; Mir Shahidul Islam; Shahin Hossain; Jannatul Nasrin; Ayub Nabi Khan (SPE Polymers)
Abstract In recent years, there has been a significant push toward using environment‐friendly composite materials derived from renewable resources. Areca nut husk and bagasse fibers are excellent examples of agricultural by‐products that possess valuable properties for various applications. In this work, three samples containing 23.06%, 28.54%, and 33.33% of areca nut husk and bagasse fibers‐reinforced epoxy matrix (ABFR) hybrid composites were prepared to assess their suitability for use as thermally insulated false ceilings in affordable housing, civil structures, and the automotive industry. The novel hybrid composites were characterized by tensile strength, flexural strength, morphology, thermal conductivity, thermogravimetric analysis (TGA), and percentage of water absorption. The composite containing 23.06% fiber exhibited the lowest thermal conductivity at 0.1631 W/m K and demonstrated excellent thermal insulating properties at 0.03629%. It achieved a maximum tensile strength of 30.05 MPa and a flexural strength of 19.72 MPa. The thermogravimetric analysis indicated that the composites undergo multiple degradation steps; however, they remain stable within the temperature range of 280–328°C. The scanning electron microscope (SEM) observations revealed effective interfacial bonding between the fibers and the epoxy matrix. These characteristics suggest that this hybrid composite could be a suitable option for thermally insulated false ceilings when compared to existing synthetic fiber alternatives. Highlights The study aims to create eco‐friendly composites from areca nut husk and bagasse fiber. The hybrid composite containing 23.06% fiber showed the lowest thermal conductivity and best insulation, ideal for ceilings. More fiber in composites increased water absorption, balancing insulation with resistance. SEM micrographs clarify the proper bonding between resin and reinforcing material. Mechanical tests demonstrate superior strength and durability.